DEVELOPMENT OF CONTEXTUAL-BASED BIOLOGY BOOKLET CONTAINING MATERIAL ON THE STRUCTURE AND FUNCTION OF PLANT TISSUES FOR JUNIOR HIGH SCHOOL STUDENTS - Annisa Jaya Fitri; Ristiono Ristiono; Helendra Helendra; Yosi Laila Rahmi (ATRIUM PENDIDIKAN BIOLOGI, 2021)
This study aims to develop a science-biology booklet contextual-based in structure and function of plant tissue for grade VIII students of SMP/MTs which are valid and practical for use in learning. The type of research is Research and Development (R&D) with a 4-D development model (four-D model). This Science-Biology booklet was validated by four validators. The practicality test subjects of this study were 17 people, consisting of 15 students and two teachers of SMP Negeri 30 Padang. The results showed that the validity value of the booklet was 91.04% with very valid criteria and the practicality value of the booklet was 95.38% by the teacher and 98.14% by students with very practical criteria. Based on the results of the study, it can be concluded that the booklet developed is of good quality and achiev the booklet's eligibility standards so that it can increase students' conceptual understanding independently of their respective learning speed that have correlation with their dialy life.